IMPLEMENTASI AKAD IJARAH PADA TRANSAKSI JUAL BELI BUKET UANG DI RN BUKET DAN NEPI BUKET BERDASARKAN PANDANGAN MUI TULUNGAGUNG - Sari, Linda Puspita; Aridho, Muhammad Firdaus; Andhiyan, Trian; Rifai, Mohammad Saiful; Puspita Sari, Linda (LPPM STAI Muhammadiyah Probolinggo, 2026)
This research aims to analyze the implementation of the ijarah contract in the money bouquet business in Tulungagung Regency, specifically focusing on RN Buket and Nepi Buket, with reference to the legal review by the Tulungagung Indonesian Ulema Council (MUI). The phenomenon of using cash as decorative objects requires legal clarity to avoid usury (riba) and uncertainty (gharar). A descriptive qualitative method was employed, with data gathered through observation, documentation, and in-depth interviews with business owners and representatives of the Fatwa Commission of MUI Tulungagung. The data were then visually validated using NVivo software. The research findings indicate that transactions in both MSMEs are declared valid according to the view of MUI Tulungagung as they meet the criteria of the ijarah (service) contract. The sellers' profits are derived purely from assembly fees and raw material costs rather than the difference in the money's nominal value. Furthermore, price transparency and the use of protective plastic to maintain the physical integrity of the money align with the principles of liability (dhaman) and maqashid sharia in the aspect of hifdz al-mal (safeguarding wealth). The confirmation from MUI Tulungagung serves as a reinforcement that this business is sharia-compliant as long as the nominal value of the money is not traded and the physical money remains protected.